Creative industries and their role in the creative value chain - A comparative study of SMEs in Canada and Thailand - Veera Bhatiasevi (2018)
© 2014 Inderscience Enterprises Ltd. The terms 'creative economy' and 'creative industries' refer to emerging models of development that play a major role in both creativity and in the intellectual capital for economic development, while the creative value chain is one of the most straightforward and widely recognised methods used in analysing the structure and function of creative industries. This paper has three objectives: 1) to identify the role of SMEs in the creative value chain; 2) to compare the role of SMEs in the creative value chain in Canada and Thailand; 3) to identify the challenges that Thai SMEs face in the creative value chain and to see what lessons can be learned from Canadian SMEs. This research is one of the first studies to compare the role of SMEs in the creative value chain, especially in the context of a comparative study between a developed and a developing country. Copyright